Facilitators and barriers to implementing pharmacist-prescribed hormonal contraception in California independent pharmacies. Issue 3 (15th March 2020) - Gomez, Anu Manchikanti; McCullough, Colleen; Fadda, Rafaela; Ganguly, Brittany; Gustafson, Elena; Severson, Nicolette; Tomlitz, Jacob
ABSTRACT: In 2013, California passed legislation to expand the scope of pharmacist practice, including authorizing pharmacists to prescribe hormonal contraception. Pharmacist-prescribed contraception was largely unavailable across the state in 2017. This study aimed to identify barriers and facilitators to offering this service in California independent pharmacies. To do so, we thematically analyzed qualitative data from structured interviews with 36 pharmacists working in independent pharmacies in 2016–17. We found that pharmacists anticipated general benefits from expanding their roles to prescribe contraception, including increasing health care access and decreasing costs. In contrast, described barriers were concrete, including lack of financial incentives and business risks for independent pharmacies. Specific barriers to prescribing hormonal contraception included time required to screen and counsel women about contraception and concerns that pharmacist-prescribed contraception would increase liability and lead to patients seeking health care less frequently. This study suggests that incentives and barriers identified by the respondents are likely to have varied and unequal impacts, with immediate barriers being potentially prohibitive for pharmacists to prescribe contraception. For independent pharmacies, perceived business risks and lack of insurance reimbursement may outweigh professional support for prescribing contraception, limiting the public health impact of legislation that should increase contraceptive access.